On teaching Americans to play mbira like Zimbabweans - Azim, Erica (International Library of African Music, 1999)
In teaching the 1,000-year old Shona mbira tradition of Zimbabwe, I have discovered that Western students have great difficulty in learning to hear mbira music in a Shona way. Though Western students are able to learn to play basic traditional parts, it often takes them years to master the more difficult cross-cultural aspects of the music, including the style of improvisation. Improvising in a Shona way is dependent upon hearing in a Shona way.
Keywords: Shona (African people); Mbira; Mbira music; Musical instruments; African Music; Zimbabwe; Mbira (Instrument)